Visual Effects Analysis in Building Messages Through Sequence in Anti-Hero Music Video - Sanjaya, William (VCD, 2025)
Visual effects are image manipulation and the creation of illusions from shooting that lead the audience to see the illusion of reality in the scenes. Visual effects can dramatize scenes so that messages can be conveyed to the audience. Thus, visual effects that are created in the right context could enhance the overall story. "AntiHero" is a music video that tells a story about nightmares and disturbances in the mind that change situations in real life. As a director and songwriter, taylor swift used visual effects to dramatize the scene through narrative point, so that messages of song’s lyric could be conveyed to the audience. This study was conducted to discuss the application of visual effects in building messages through the story stage in the music video "Anti-Hero". This research used qualitative method with purposive sampling approach. The theory used is the theory of visual effects proposed by Eran Dinur. The study was conducted by describing the sequence, song lyrics, and types of visual effects applied from director and songwriter’s point of view. From the results of the study, it can be concluded that there is an application of visual effects in the form of morphing, cloning, and giant effects that occur throughout the music video. The application of morphing shows the unreal world and wounds experienced by Taylor at the beginning of the story. The clone effect shows the different nature or "anti-hero" of Taylor Swift. The giant effect shows a different nature in size, making Taylor isolated from those around her. Taylor Swift, as both director and songwriter, utilized visual effects to convey profound messages from the lyric of her song through the narrative of each scene. Swift’s storytelling prowess extends beyond mere narrative planning, as she skillfully integrates various visual effects to enhance the impact of her lyrics. By employing diverse characters, both “good” and “bad Taylor”, with distinct characteristics within her surreal world, Taylor elevates her storytelling to new heights. The seamless integration of visual effects throughout the sequences ensures that the song’s lyrics are effectively conveyed, creating a cohesive and immersive experience for the audience.